Exogenous Wnt1 Prevents Acute Kidney Injury and Its Subsequent Progression to Chronic Kidney Disease - Hong, Xue; Zhou, Yanni; Wang, Dedong; Lyu, Fuping; Guan, Tianjun; Liu, Youhua; Xiao, Liangxiang (Frontiers in Physiology, 2021)
Studies suggest that Wnt/β-catenin agonists are beneficial in the treatment of acute kidney injury (AKI); however, it remains elusive about its role in the prevention of AKI and its progression to chronic kidney disease (CKD). In this study, renal Wnt/β-catenin signaling was either activated by overexpression of exogenous Wnt1 or inhibited by administration with ICG-001, a small molecule inhibitor of β-catenin signaling, before mice were subjected to ischemia/reperfusion injury (IRI) to induce AKI and subsequent CKD. Our results showed that in vivo expression of exogenous Wnt1 before IR protected mice against AKI, and impeded the progression of AKI to CKD in mice, as evidenced by both blood biochemical and kidney histological analyses. In contrast, pre-treatment of ICG-001 before IR had no effect on renal Wnt/β-catenin signaling or the progression of AKI to CKD. Mechanistically, in vivo expression of exogenous Wnt1 before IR suppressed the expression of proapoptotic proteins in AKI mice, and reduced inflammatory responses in both AKI and CKD mice. Additionally, exogenous Wnt1 inhibited apoptosis of tubular cells induced by hypoxia-reoxygenation (H/R) treatment in vitro. To conclude, the present study provides evidences to support the preventive effect of Wnt/β-catenin activation on IR-related AKI and its subsequent progression to CKD.